2010
DOI: 10.1039/b914230d
|View full text |Cite
|
Sign up to set email alerts
|

Size control and immobilization of gold nanoparticles stabilized in an ionic liquid on glass substrates for plasmonic applications

Abstract: Gold (Au) nanoparticles were prepared by sputter deposition of Au metal in an ionic liquid (IL) of 1-butyl-3-methylimidazolium hexafluorophosphate (BMI-PF6). The size of Au nanoparticles was increased from 2.6 to 4.8 nm by heat treatment at 373 K. The nanoparticles uniformly dispersed in the IL were densely immobilized on a glass substrate surface modified with a silane coupling agent having an imidazole functional group by spreading the Au particle IL solution on the substrates, followed by heat treatment at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 44 publications
(52 reference statements)
3
62
0
Order By: Relevance
“…Future challenge in this field will be how we collect the metal nanoparticles suspended in RTILs and how we develop a metal nanoparticle mass production method. Regarding the former matter, we found a facile way that is adsorption of the suspended nanoparticles on a solid substance (Kameyama et al, 2010;Okazaki et al, 2009;Tsuda et al, 2009b;Tsuda et al, 2010b). Nanoparticles are stably suspended in RTIL by the interaction with ionic species exciting around the nanoparticles.…”
Section: Future Difficuties About the Rtil-magnetron Sputtering Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future challenge in this field will be how we collect the metal nanoparticles suspended in RTILs and how we develop a metal nanoparticle mass production method. Regarding the former matter, we found a facile way that is adsorption of the suspended nanoparticles on a solid substance (Kameyama et al, 2010;Okazaki et al, 2009;Tsuda et al, 2009b;Tsuda et al, 2010b). Nanoparticles are stably suspended in RTIL by the interaction with ionic species exciting around the nanoparticles.…”
Section: Future Difficuties About the Rtil-magnetron Sputtering Methodsmentioning
confidence: 99%
“…Figure 3 shows a schematic illustration of this method that uses a common magnetron sputtering apparatus except for the use of RTIL as a substrate. This method has achieved the preparation of various pure metal nanoparticles, such as Au Hatakeyama et al, 2010;Kameyama et al, 2010;Khatri, et al, 2008;Okazaki et al, 2009;Shishino et al, in press;Torimoto et al, 2006;Wender et al, 2010), Ag Suzuki et al, 2009), Pt (Tsuda et al, 2009b;Tsuda et al, 2010b), In (Suzuki et al, in press) etc., possessing particle sizes less than 10 nm in diameter without any specific stabilizing agent. Small-angle X-ray scattering study revealed initial formation mechanism of the gold nanoparticles during the sputtering process onto several 1,3-dialkylimidazolium tetrafluoroborate ).…”
Section: Magnetron Sputtering Onto Rtilmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Au-NPs were prepared by sputter deposition of Au metal in [BMIm] [PF 6 ]. The size of Au nanoparticles was increased from 2.6 to 4.8 nm by heat treatment at 373 K [175].…”
Section: -By Magnetron Sputteringmentioning
confidence: 99%
“…[9][10][11][12][13][14] Moreover, in the case of sputtering deposition onto ILs, very stable spherical NPs are easily prepared by simply adjusting the physical parameters during the sputtering process, allowing for control of the NPs size and size distribution without the addition of extra stabilisers. 15 However, the factors that govern NPs growth in the sputtering process are still unclear. In fact, recent reports suggest that NPs nucleate and grow on the IL surfaces, 16 as also observed for sputtering onto castor oil.…”
Section: Introductionmentioning
confidence: 99%